Accident scenario modelling with hazardous materials in transportation infrastructures. Issue 4 (18th September 2020) - Reis, Johnny; Ribeiro, Carlos; Rodrigues, Daniel; Rodrigues, André
Abstract : The development and well-being of industrialised societies require constant coexistence with hazardous materials. These can be found in different physical states, under very different conditions of pressure and temperature, stored inside industrial units and commercial spaces with different characteristics, in the most varied conventional means of communication or in transport conduits deployed throughout the territory, greatly contributing to the territorial dispersion of these substances. This study focused on Mortágua Municipality, which is in the Central Region of Portugal. To develop this work, the authors analysed the infrastructures that support the transport of dangerous substances, the types of dangerous substances that circulate and how frequently they are transported. Then, the Aloha software was used to simulate the occurrence of an accident in each infrastructure, motivating three different analyses: the propagation of a toxic cloud, a flammable cloud and thermal radiation caused by a boiling liquid expanding vapour explosion or jet fire. The results obtained show a lack of information on some of the types of transport for these dangerous substances, and when these data exist, they are not properly handled. However, it can be concluded that if an accident occurs in the presented municipality, the socio-economic losses will be very high.